Electronic Properties of Adsorption of CO, CO2, OH, and B2 on Nitrogen Doped Graphene Nanosheets as a Gas Sensor Application for Harmful Gases - Rajaa K. Mohammad (Journal of Global Pharma Technology, 2016)
In the present work, the sensitivity of hybrid nitrogen-graphene nanosheet (Ndoped graphene) toward a series of small gas molecules (CO, CO2, OH, and B2) has been calculated based on the first-principles calculations. The properties that have been investigated are the density of state, IR spectra, and the electronic and structural properties. Interestingly, we observed that the adsorptions of (CO, CO2, OH, and B2) on the N-doped graphene are small physisorption with adsorption energy (Ead) between 0.75 to 1.15 eV, whereas the adsorption of CO on N doped graphene is high chemisorptions. The adsorption of CO and CO2 on the electronic properties lead to a decreasing in the highest occupied molecular orbital (EHOMO) and lowest unoccupied molecular orbital (ELUMO) and Fermi energy (Ef), and increasing in the energy band gap (Eg). Our findings indicate the possibility of using this nanosheet as a gas sensor for harmful gases (CO, CO2).Keywords: Electronic properties, Nitrogen- graphene nanosheet, Gas sensor, Harmful gases.